2018
DOI: 10.1080/09540121.2018.1492699
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamics of ART adherence in the context of a mindfulness instruction intervention among youth living with HIV in Baltimore, Maryland

Abstract: Youth living with HIV have sub-optimal rates of adherence to antiretroviral therapy (ART). Mindfulness instruction interventions have shown promise for improving medication adherence, but the effects and mechanisms of these interventions are still being explored among people living with HIV, including youth. In the context of a randomized controlled trial of the efficacy of a Mindfulness-Based Stress Reduction (MBSR) program on ART adherence and viral suppression among youth living with HIV, we conducted 44 it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…16 Studies have demonstrated improved adherence with mobile games, web-based interventions, interactive text message reminders, and mindfulness interventions in the US ALWHIV. [17][18][19][20] Several additional studies investigating novel approaches for ALHIV engagement in care are ongoing. [21][22][23][24] These interventions should be studied in pregnancy as well.…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies have demonstrated improved adherence with mobile games, web-based interventions, interactive text message reminders, and mindfulness interventions in the US ALWHIV. [17][18][19][20] Several additional studies investigating novel approaches for ALHIV engagement in care are ongoing. [21][22][23][24] These interventions should be studied in pregnancy as well.…”
Section: Discussionmentioning
confidence: 99%
“…Research using process data holds important lessons for understanding why certain interventions may be easier to implement in given populations, or why some interventions may show limited evidence of effectiveness. There is a large body of evidence relating to behavioural and psychosocial interventions for ALHIV; however, these studies rarely report on mental health outcomes specifically, often focusing on treatment adherence and sexual and reproductive health outcomes [34][35][36][37]. Existing interventions tend to be specifically designed to promote adherence to ART and prevent risky sexual behaviours such as unprotected intercourse [38], which are seen as essential to supporting adolescent health and preventing onward transmission.…”
Section: Invest In High-quality Research To Test the Effectiveness mentioning
confidence: 99%
“…Adaptation to the new condition of living with HIV, manifesting as acceptance of illness (Samson & Siam, 2011), plays an important role in patients' subjective quality of life assessment (Mazurek & Lurbiecki, 2014). Additionally, previous studies have indicated that an increase in acceptance of HIV leads to improved adaptation outcomes, including ART adherence and better life quality (Kerrigan, Grieb, Ellen, & Sibinga, 2018; Oji et al., 2017); however, if PLWH lack illness acceptance, their lives with HIV may be hindered by a maladaptive state. Since little is known about the mechanisms contributing to illness acceptance among PLWH, it is important and necessary to further our understanding of these mechanisms to contribute to the development of reliable strategies for promoting positive adaptation outcomes.…”
Section: Introductionmentioning
confidence: 99%